2013
DOI: 10.4049/jimmunol.1301250
|View full text |Cite
|
Sign up to set email alerts
|

The Uncoupling of Monocyte–Platelet Interactions from the Induction of Proinflammatory Signaling in Monocytes

Abstract: Induction of an inflammatory monocyte phenotype by activated platelets is implicated in the pathogenesis of inflammatory diseases, including atherosclerosis. In this study, we investigated the early signaling events associated with this platelet-induced inflammatory phenotype. We report that coculture of human monocytes with activated platelets induces phosphorylation of Akt, together with rapid mobilization of intracellular Ca2+, and show that these signaling events can be uncoupled from monocyte binding to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 52 publications
4
38
0
4
Order By: Relevance
“…The present study revealed that HCN1 expression was not detectable in the atrial muscle of dogs in the AF or sham control groups, which may have been due to very low expression levels. The results were consistent with the findings of previous studies, including the study by Stephen et al (14). It is widely accepted that HCN3 is expressed primarily in the central nervous system and not in the heart; however, the present study did not include the detection of HCN3.…”
Section: Discussionsupporting
confidence: 93%
“…The present study revealed that HCN1 expression was not detectable in the atrial muscle of dogs in the AF or sham control groups, which may have been due to very low expression levels. The results were consistent with the findings of previous studies, including the study by Stephen et al (14). It is widely accepted that HCN3 is expressed primarily in the central nervous system and not in the heart; however, the present study did not include the detection of HCN3.…”
Section: Discussionsupporting
confidence: 93%
“…During in vitro platelet stimulation experiments using thrombin, however, monocyte interaction with activated platelets resulted in increased cytokine production [30]. Induction of pro-inflammatory signaling in monocytes by platelets was dependent on secreted platelet products, not on direct platelet-monocyte interaction as reported in another study [31]. Although cytokine production is indispensable for an adequate host response to invading pathogens, excessive cytokine production might have detrimental effects during severe infection [32].…”
Section: Discussionmentioning
confidence: 88%
“…These observations are in line with results from a recent study, showing that in response to thrombin activated platelets, not thrombin itself, trigger early signaling events (such as intracellular Ca ++ flux) in monocytes on platelet-monocyte interaction. 39 Platelet interaction with monocytes via P-selectin-PSGL-1 further increased the rate and quantity of OxLDL uptake by monocytes in a dose-dependent manner. Scavenger receptor CD36, the major receptor for OxLDL on platelets, 23,24 was mainly responsible for the platelet-mediated effects on OxLDL uptake by monocytes.…”
Section: Discussionmentioning
confidence: 95%